The World on a Globular Projection - D.F. Robinson & Co. (Hartford, Conn.) (D.F. Robinson & Co. (Hartford, Conn.), 1830)
This sheet includes a map of the northern and southern hemispheres shown as connected circles. The continents are shaded in colors and labeled including some countries, cities, and bodies of water. At the bottom of the page is "A Chart, exhibiting the progress of Christianity from the birth of our Saviour to the present time" broken down by continents.